Comparing the Bridge‐Type Zero‐Profile Anchored Spacer (ROI‐C) Interbody Fusion Cage System and Anterior Cervical Discectomy and Fusion (ACDF) with Plating and Cage System in Cervical Spondylotic Myelopathy. Issue 6 (27th April 2022) - He, Shuangjun; Zhou, Zhangzhe; Shao, Xiaofeng; Zhou, Lijian; Zhang, Changhao; Zhou, Xinfeng; Wu, Shuhua; Chen, Kangwu; Wang, Yaowei; Qian, Zhonglai
Abstract : Objective: To compare the clinical efficacy and radioactivity of the bridge‐type zero‐profile anchored spacer (ROI‐C) interbody fusion cage and anterior cervical discectomy and fusion with plating and cage system (ACDF) for cervical spondylotic myelopathy (CSM). Methods: This is a retrospective contrastive study. We recruited 35 patients who received ROI‐C (ROI‐C group) and 34 patients who received ACDF (ACDF group), between January 2014 to January 2019, at our treatment center. The ROI‐C group comprised of 11 males and 24 females with a mean age of 61.59 ± 8.21 years (range, 51–71 years). The ACDF group comprised of 12 males and 22 females with a mean age of 60.15 ± 7.52 years (range, 52–74 years). Neck Disability Index (NDI), Japanese Orthopaedic Association score (JOA), Odom's score, cervical Cobb angle, fusion rate, adjoining ossification, and dysphagia. Results: A total of 69 patients met the inclusion criteria, and these patients received more than two years of follow‐up. There were significant differences in surgical duration (101 ± 22 min vs . 118 ± 29 min) and blood loss (102 ± 46 ml vs . 145 ± 58 ml) between two groups ( P < 0.05). The JOA and NDI of these two groups of patients significantly improved, when compared with those before the operation ( P < 0.05). Twenty‐nine of 35 patients in the ROI‐C group and 27 of 34 patients in ACDF group achieved good or excellent outcomes according to Odom's criteria. The cervical lordosis of both two groups significantly increased, when compared with those before the operation ( P < 0.05). In the ROI‐C group, the postoperative fusion rate was 85.7% at the 3‐month follow‐up and 100% at the final follow‐up. In the ACDF group, the postoperative fusion rate was 82.4% at the 3‐month follow‐up and 100% at the final follow‐up. The dysphagia incidence of the ACDF group was higher than that of the ROI‐C group postoperatively and at the one month after surgery ( P < 0.05), but no significant difference was found in the incidence of dysphagia at final follow‐up ( P > 0.05). Conclusion: Both ROI‐C and ACDF achieved good therapeutic effects. However, ROI‐C can reduce the operation time and postoperative complications. Abstract : Schematic diagrams of the surgical procedure for the two operations. (A‐D) The ROI‐C operation process (E‐H) the ACDF operation process. (A) The cervical disc herniation compressing the spinal cord. (B) The removal of the herniated intervertebral discs and posterior longitudinal ligament. (C) The installation of the ROI‐C interbody fusion cages. (D) A schematic diagram of the ROI‐C after operation. (E) The removal of the herniated intervertebral discs and posterior longitudinal ligament. (F) The installation of interbody fusion cages. (G) The installation of cervical spine front titanium plate. (H) A schematic diagram of ACDF after operation.